Environment Care Character Education as a Flood Disaster Management Effort - Nina Permata Sari; Eklys Cheseda Makaria; Rochgiyanti Rochgiyanti; Muhammad Andri Setiawan (STAI Hubbulwathan Duri, 2021)
Character education awakens the realm of values and norms of students. Environmental care is one of the 18 character values in the Indonesian Ministry of Education and National (2010) character education design. This article aims to examine the character of caring for the environment to mitigate flood disasters. Qualitative approach with descriptive method is used to describe research problems. Miles and Huberman's interactive model reduced interview data, presented descriptive narratives, and document research results. Triangulation techniques and research extension resulted in data saturation. The results of the study describe that related to the environmental care behavior of the community in Pengaron Village, it is described as follows; 1) The attitude of the community towards flood prevention is to do cooperation every week by coordinating through village officials, 2) Knowledge about flooding is passed down from generation to generation to children. This information includes the fact that floods always occur every year, so people must always be alert; 3) Environmental care behavior includes the obligation to have swimming skills, construct houses on stilts and or two floors, and plant trees that have characteristics sensitive to weather changes. Society inherits the character of caring for the environment as the primary value in everyday life. The character of caring for the environment contributes to educating the importance of preserving and coexisting with the environment.